Cholinergic Nociceptive Mechanisms in Rat Meninges and Trigeminal Ganglia: Potential Implications for Migraine Pain - Shelukhina, Irina; Mikhailov, Nikita; Abushik, Polina; Nurullin, Leniz; Nikolsky, Evgeny E.; Giniatullin, Rashid (Frontiers in Neurology, 2017)
Background Parasympathetic innervation of meninges and ability of carbachol, acetylcholine (ACh) receptor (AChR) agonist, to induce headaches suggests contribution of cholinergic mechanisms to primary headaches. However, neurochemical mechanisms of cholinergic regulation of peripheral nociception in meninges, origin place for headache, are almost unknown. Methods Using electrophysiology, calcium imaging, immunohistochemistry, and staining of meningeal mast cells, we studied effects of cholinergic agents on peripheral nociception in rat hemiskulls and isolated trigeminal neurons. Results Both ACh and carbachol significantly increased nociceptive firing in peripheral terminals of meningeal trigeminal nerves recorded by local suction electrode. Strong nociceptive firing was also induced by nicotine, implying essential role of nicotinic AChRs in control of excitability of trigeminal nerve endings. Nociceptive firing induced by carbachol was reduced by muscarinic antagonist atropine, whereas the action of nicotine was prevented by the nicotinic blocker d-tubocurarine but was insensitive to the TRPA1 antagonist HC-300033. Carbachol but not nicotine induced massive degranulation of meningeal mast cells known to release multiple pro-nociceptive mediators. Enzymes terminating ACh action, acetylcholinesterase (AChE) and butyrylcholinesterase, were revealed in perivascular meningeal nerves. The inhibitor of AChE neostigmine did not change the firing per se but induced nociceptive activity, sensitive to d-tubocurarine, after pretreatment of meninges with the migraine mediator CGRP. This observation suggested the pro-nociceptive action of endogenous ACh in meninges. Both nicotine and carbachol induced intracellular Ca2+ transients in trigeminal neurons partially overlapping with expression of capsaicin-sensitive TRPV1 receptors. Conclusion Trigeminal nerve terminals in meninges, as well as dural mast cells and trigeminal ganglion neurons express a repertoire of pro-nociceptive nicotinic and muscarinic AChRs, which could be activated by the ACh released from parasympathetic nerves. These receptors represent a potential target for novel therapeutic interventions in trigeminal pain and probably in migraine.